Stakeholders’ Contribution in Coordination of Passengers’ and Goods’ Flows within the Urban Areas - Rześny-Cieplińska, Jagienka (European Journal of Sustainable Development, 2018)
Cities are becoming congested due to migration from rural areas, emigration from overseas as a result of globalization. The inspiration for the research problem discussed in this study is increasing need of looking for the solutions in improving mobility within the urban areas. With the growth of cities and urban population, city authorities all over the world focus on preparing the conditions for better living in urban areas. But it can’t be forgotten, the local authorities are only the part of all actors engaged and exposed to mobility problems. The main aim of the study is to find out how to solve problems of improving passengers’ and goods’ mobility in Polish urban areas. After defining all groups of parties involved in mobility problems, the author is going to achieve the goal by conducting semi-structured interviews with urban-planning and sustainability experts as well as government officials and other groups of stakeholders. Moreover the research is going to be carried out on the analysis of the practical solutions in the field of mobility in cities in European urban areas, documents of the European Commission and the publications prepared by industry associations. The theoretical part of the paper is based on the existing materials from public resources and author’s research experience. The findings of the research is going to present the solutions of the better and more sustainable mobility in urban areas that can be successfully implemented in Polish cities in the area of mobility while meetings the demands of all stakeholders engaged. Keywords: transport organization, metropolitan areas, city logistics